2010
DOI: 10.1073/pnas.0910410107
|View full text |Cite
|
Sign up to set email alerts
|

Bovine cytochrome c oxidase structures enable O 2 reduction with minimization of reactive oxygens and provide a proton-pumping gate

Abstract: The O 2 reduction site of cytochrome c oxidase (CcO), comprising iron (Fe a 3 ) and copper (Cu B ) ions, is probed by x-ray structural analyses of CO, NO, and CN - derivatives to investigate the mechanism of the complete reduction of O 2 . Formation of the derivative contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
213
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(224 citation statements)
references
References 30 publications
11
213
0
Order By: Relevance
“…In this study, we determined the structure of the CN À -bound fully oxidized form at 2.0 Å resolution. It should be noted that the X-ray structure of CN À -bound mammalian CcO in the fully reduced state, which was distinctively different from the fully oxidized mammalian CcO in the structure around the haem a 3 -Cu B , including Tyr244, has previously been reported (Muramoto et al, 2010), but to date the structure of the CN À -bound fully oxidized state has not been reported. Comparison of this structure with that of the fully oxidized enzyme previously determined revealed that X-ray irradiation, which induces the accumulation of water in the vicinity of Tyr244, does not induce any significant change in the protein structure.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, we determined the structure of the CN À -bound fully oxidized form at 2.0 Å resolution. It should be noted that the X-ray structure of CN À -bound mammalian CcO in the fully reduced state, which was distinctively different from the fully oxidized mammalian CcO in the structure around the haem a 3 -Cu B , including Tyr244, has previously been reported (Muramoto et al, 2010), but to date the structure of the CN À -bound fully oxidized state has not been reported. Comparison of this structure with that of the fully oxidized enzyme previously determined revealed that X-ray irradiation, which induces the accumulation of water in the vicinity of Tyr244, does not induce any significant change in the protein structure.…”
Section: Introductionmentioning
confidence: 97%
“…The results are consistent with the maintenance of the oxidized protein conformation (36), even though the metal centers are reduced, before annealing at warmer temperature allows the protein to change its structure. The strained configuration shows an interesting spectral feature at 589 nm, also observed in the bovine and thermus CcO irradiated crystals (34,37). Other spectral methods such as single-crystal low-temperature EPR or resonance Raman will be needed to determine the nature of this form; the Soret region of the spectrum, which could provide some clues, absorbs too strongly to be measured (Fig.…”
Section: S142mentioning
confidence: 99%
“…The typical examples are cytochrome c oxidase and laccase, their active sites contain the similar metal clusters of assembled Cu 2 þ complexes 19,20 . Previous work showed that laccase in vitro is more desirable as the quasichampion potential (onset at 1.2 V versus reversible hydrogen electrode (RHE), pH ¼ 4) is observed on its modified electrode 21 , suggesting that Cu 2 þ ion is supposed to be an ideal catalytic site as long as the energy level of the d-electrons is tuned to a reasonable state.…”
mentioning
confidence: 99%